An emerging research: the role of hepatocellular carcinoma-derived exosomal circRNAs in the immune microenvironment - Xu, Huang-Zhen; Lin, Xin-Yi; Xu, Yun-Xian; Xue, Hui-Bin; Lin, Shu; Xu, Tian-Wen (Frontiers in Immunology, 2023)
Hepatocellular carcinoma (HCC), the most common primary malignancy of the liver, is one of the leading causes of cancer-related death and is associated with a poor prognosis. The tumor microenvironment (TME) of HCC comprises immune, immunosuppressive, and interstitial cells with hypoxic, angiogenic, metabolic reprogramming, inflammatory, and immunosuppressive features. Exosomes are nanoscale extracellular vesicles that secrete biologically active signaling molecules such as deoxyribonucleic acid (DNA), messenger ribonucleic acid (mRNA), microribonucleic acid (miRNA), proteins, and lipids. These signaling molecules act as messengers in the tumor microenvironment, especially the tumor immunosuppressive microenvironment. Exosomal circRNAs reshape the tumor microenvironment by prompting hypoxic stress response, stimulating angiogenesis, contributing to metabolic reprogramming, facilitating inflammatory changes in the HCC cells and inducing tumor immunosuppression. The exosomes secreted by HCC cells carry circRNA into immune cells, which intervene in the activation of immune cells and promote the overexpression of immune checkpoints to regulate immune response, leading tumor cells to acquire immunosuppressive properties. Furthermore, immunosuppression is the final result of a combination of TME-related factors, including hypoxia, angiogenesis, metabolic reprogramming, and inflammation changes. In conclusion, exosomal circRNA accelerates the tumor progression by adjusting the phenotype of the tumor microenvironment and ultimately forming an immunosuppressive microenvironment. HCC-derived exosomal circRNA can affect HCC cell proliferation, invasion, metastasis, and induction of chemoresistance. Therefore, this review aimed to summarize the composition and function of these exosomes, the role that HCC-derived exosomal circRNAs play in microenvironment formation, and the interactions between exosomes and immune cells. This review outlines the role of exosomal circRNAs in the malignant phenotype of HCC and provides a preliminary exploration of the clinical utility of exosomal circRNAs.